A smart energy consumption manager based on protues simulation - Mohammed Abdulhussein Mohammed; Alaa Desher Farhood; Ahmed Jabbar Abid (Institute of Advanced Engineering and Science, 2020)
In the proposed system, a strategy for the control of energy consumption by home appliances is provided. The statistics of previous energy production and consumption of a case study city are used in providing the strategy. In the design of the proposed system, home appliances are categorized into three levels of priority, even though it can be more than three. In this article the control of energy consumption is achieved using a real time energy consumption manager (ECM) based on stored data without the need for real time communication. The system which is proposed here is affordable and simple. Also, it does not require grid upgrade or power line communication through the grid.